2009
DOI: 10.1111/j.1365-2222.2009.03386.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 and cysteinyl leukotriene concentrations in sputum: association with asthma severity and eosinophilic inflammation

Abstract: Increased airway concentrations of PGE(2) are consistent with the hypothesis that PGE(2) has a bronchoprotective and anti-inflammatory role in patients with more severe asthma. A reduced PGE(2) to cysLT ratio in the airways may adversely affect lung function and contribute to persistence of symptoms and airway remodelling in patients with eosinophilic airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 40 publications
(60 reference statements)
2
45
0
2
Order By: Relevance
“…Therefore, the role of EP4 receptors in endothelial function awaits further investigation. In summary, increased levels and protective effects of PGE 2 in pulmonary inflammatory diseases have been described previously [14,46]. The accumulation of eosinophils in asthmatic airways greatly contributes to the outcome of the disease by releasing cytotoxic mediators, leading to airway remodeling and angiogenesis in the chronically inflamed pulmonary tissue [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the role of EP4 receptors in endothelial function awaits further investigation. In summary, increased levels and protective effects of PGE 2 in pulmonary inflammatory diseases have been described previously [14,46]. The accumulation of eosinophils in asthmatic airways greatly contributes to the outcome of the disease by releasing cytotoxic mediators, leading to airway remodeling and angiogenesis in the chronically inflamed pulmonary tissue [7].…”
Section: Discussionmentioning
confidence: 99%
“…While PGD 2, which is the predominant PG formed in mast cells, exerts proinflammatory effects by regulating the recruitment of eosino-phils, basophils, and Th2 lymphocytes to the sites of allergic inflammation [12], PGE 2 seems to attenuate inflammatory responses and reduce tissue injury in airways [13]. PGE 2 was found to exert bronchoprotective effects in patients with asthma [14]. In rats, the ovalbumin-induced early and late phase airway responses were inhibited by intratracheally administered PGE 2 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, TP-dependent effects become magnified in the setting of inflammation if the capacity to up-regulate PGE 2 generation (or to signal through EP receptors) is impaired. Deficient PGE 2 may potentiate AHR in the setting of eosinophilic inflammation (15,47). Defective COX-2-dependent production of PGE 2 and deficient expression of EP 2 receptors have both been documented in AERD (19,21,48), and might account for the marked eosinophilic airway inflammation and high basal levels of leukotriene E 4 typical of this syndrome.…”
Section: Pge 2 Deficiency Augments Icam-1-dependent Pulmonary Leukocytementioning
confidence: 99%
“…[52][53][54] Although it is reported that IL-13 inhibits PGE 2 synthetic pathways and decreases PGE 2 secretion in HBE cells, 55 a clinical study showed that cysLT and PGE 2 concentrations in sputum are higher in those with asthma than in control subjects. 56 PGE 2 also promotes cell growth in bronchial epithelial cells. 57 We showed that, consistent with this, PGE 2 secretion was increased during the cell growth and diff erentiation phase of HBE cells.…”
Section: Secretion In Goblet-enriched Cellsmentioning
confidence: 99%